Strategi Pengembangan Produk Untuk Meningkatkan Pendapatan UMKM Lasehan La Bagus - Juniarty, Mira; Nuraulia; Khairunnisa; Dillah, Ubai (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Business development is the same as developing activities, developing products, sales, developing consumers, increasing profits, as well as developing product value, product benefits and product distribution. This research aims to analyze product development strategies to increase the income of MSMEs in Lasehan La Bagus. Data collection methods use interviews and observation. The key informants in this research were employees of MSME Lasehan La Bagus. This research uses qualitative analysis techniques. The survey results revealed that the product development strategy carried out by MSME Brownies Ayu Wulandari was to add or expand new product lines and also complementary product lines. Apart from that, external factors also play a role in encouraging the development of more effective products to increase MSME income